2017
DOI: 10.1371/journal.pone.0180823
|View full text |Cite
|
Sign up to set email alerts
|

A context for the last Neandertals of interior Iberia: Los Casares cave revisited

Abstract: Introduction and objectivesAlthough the Iberian Peninsula is a key area for understanding the Middle to Upper Paleolithic transition and the demise of the Neandertals, valuable evidence for these debates remains scarce and problematic in its interior regions. Sparse data supporting a late Neandertal persistence in the Iberian interior have been recently refuted and hence new evidence is needed to build new models on the timing and causes of Neandertal disappearance in inland Iberia and the whole peninsula. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 90 publications
0
20
0
4
Order By: Relevance
“…The number of “late” Neanderthal sites (<42 ka cal BP) has diminished substantially since the application of new dating techniques showed them to be much older (>42 ka cal BP) than previously thought ( 30 33 ). Across central Spain, there are no Neanderthal remains or Middle Paleolithic sites dated after 42 ka cal BP ( 34 36 ). At present, Gruta da Oliveira, Cueva Antón, and Gorham’s Cave remain the only “late” Neanderthal sites in southern Iberia dated ∼37 ka cal BP or later ( 21 , 22 ).…”
mentioning
confidence: 99%
“…The number of “late” Neanderthal sites (<42 ka cal BP) has diminished substantially since the application of new dating techniques showed them to be much older (>42 ka cal BP) than previously thought ( 30 33 ). Across central Spain, there are no Neanderthal remains or Middle Paleolithic sites dated after 42 ka cal BP ( 34 36 ). At present, Gruta da Oliveira, Cueva Antón, and Gorham’s Cave remain the only “late” Neanderthal sites in southern Iberia dated ∼37 ka cal BP or later ( 21 , 22 ).…”
mentioning
confidence: 99%
“…New data for the timing of the Middle-to-Upper Palaeolithic transition in Iberia Different models have been proposed for the timing and nature of the Middle-to-Upper Palaeolithic transition in Iberia, based on radiometric dating of archaeological layers and lithic assemblage technology. The reevaluation of the stratigraphical contexts and the application of new dating procedures have led some authors to consider that Neanderthal populations did not survive much longer in the Iberian Peninsula than in the rest of Europe (Maroto et al, 2012;Wood et al, 2013;Higham, et al, 2014;Alcaraz-Castaño et al, 2017). Based on luminescence dating of loess deposits from the Upper Tagus Basin, it has been suggested that the abandonment of the interior of Iberia by Neanderthals occurred 42 ka ago, and that, as a direct consequence of a pronounced environmental aridity, inner territories were uninhabited until 28 or 25.5 ka.…”
Section: Cultural Attribution Of Lithic Assemblagesmentioning
confidence: 99%
“…Archaeological sites in caves or rock shelters are located from 700 to 1280 masl over riverbeds or ravines, passages between valleys and plateaus or places where there is a broad visual domain or that form a sort of natural trap. Some of them have been interpreted as being sites of extended or repeated stays, such as La Ermita and Cueva Millán (Moure and García-Soto, 1982;Díez et al, 2008), Peña Miel (Utrilla et al, 1987), Los Casares (Barandiarán, 1973;Alcaraz-Castaño et al, 2017) and La Quebrada (Villaverde et al, 2017). They reveal more or less structured hearths and anthropic fractures in bones that accompany the recovered lithic assemblages.…”
Section: Archaeological Frameworkmentioning
confidence: 99%
“…The abandonment of these territories, apparently independent of the arrival of first modern humans, is linked with the onset of hostile climatic conditions characterized by the driest conditions of the last glacial period (except an even drier period linked to H3) that precedes the onset of H4. No archaeological or palaeoanthropological evidence attests to a Neanderthal presence in the whole interior of Iberia since 42 ka ago (Alcaraz-Castaño et al, 2017;Wolf et al, 2018).…”
Section: The End Of the Neanderthal Occupations In The Iberian Systemmentioning
confidence: 99%